Hydrogeochemistry of Fluorine in Groundwater in Humid Mountainous Areas: A Case Study at Xingguo County, Southern China. (15th July 2021) - Liu, Jinhui; Wang, Xinfeng; Xu, Weidong; Song, Mian; Gong, Lei; Zhang, Mengnan; Li, Linbo; He, Lishan
Abstract : The understanding of F − concentration in groundwater in humid areas is limited although there are lots of research on high-fluoride groundwater in arid areas. In this paper, with controlling factors of F − concentrations in humid areas as the focus, 130 groundwater samples, obtained from four subsystems in Northwest Xingguo County, Jiangxi Province, China, were investigated to demonstrate the controlling factors of F − concentrations in humid areas. According to analytical results, the following hydrogeochemical characteristics of the fluorine in humid mountainous areas were determined: (1) F − concentration is positively correlated with total dissolved solids (TDS), Ca 2+, HCO 3 −, and pH; (2) the groundwater features a high flow rate and low TDS; (3) the equilibrium constant of CaF2 is less than its solubility product constant, and the fluorine-bearing minerals in rocks are in a dissolved state; and (4) the dissolved fluoride-bearing minerals constitute the main sources of F − in the groundwater. Fluorine mainly comes from groundwater fluorine-bearing minerals in metamorphic rocks. Moreover, the low F − concentration in the groundwater mainly results from the fast flow rate of groundwater. Fluoride in groundwater has great potential hazards in humid areas.